2022
DOI: 10.1155/2022/7212852
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Diagnostic Value of Immune-Related Genes in Interstitial Fibrosis and Tubular Atrophy after Kidney Transplantation

Abstract: Background. Inflammation within areas of interstitial fibrosis and tubular atrophy (IF/TA) is associated with kidney allograft failure. The aim of this study was to reveal new diagnostic markers of IF/TA based on bioinformatics analysis. Methods. Raw data of IF/TA samples after kidney transplantation and control samples after kidney transplantation were extracted from the Gene Expression Omnibus (GEO) database (GSE76882 and GSE120495 datasets), and genes that were differentially expressed between the two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, Gene scoring was used to eliminate batch effects in four data sets, which enabled our prediction model to show good predictive power in both the modeling and 3 validation groups. Our study shows that our model has a predictability (AUC = 0.956) superior to another IFTA forecasting model integrated COX regression model with LASSO constructed by Yang et al (AUC = 0.8210) (11). Moreover, the AUC of the predictive model achieved 0.938 in the validation set GSE53605, 0.781 in set GSE76882, and 0.720 in set GSE22459, which suggested that our model has a high level of accuracy without over tting.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Furthermore, Gene scoring was used to eliminate batch effects in four data sets, which enabled our prediction model to show good predictive power in both the modeling and 3 validation groups. Our study shows that our model has a predictability (AUC = 0.956) superior to another IFTA forecasting model integrated COX regression model with LASSO constructed by Yang et al (AUC = 0.8210) (11). Moreover, the AUC of the predictive model achieved 0.938 in the validation set GSE53605, 0.781 in set GSE76882, and 0.720 in set GSE22459, which suggested that our model has a high level of accuracy without over tting.…”
Section: Discussionmentioning
confidence: 48%
“…In previous study of IFTA diagnosis based on mRNA expression, the quantity of samples and the method of ltering variables are limited, resulting in relatively low sensitivity and speci city (11). With the progress of machine learning algorithms, new approaches can be employed to diagnose diseases.…”
Section: Introductionmentioning
confidence: 99%
“…ANGPTL3's involvement in various renal pathologies, including diabetic nephropathy [ 6 ], renal cell carcinoma [ 7 ] and acute kidney injury [ 8 ] has been documented. From a bioinformatics perspective, Yang et al [ 9 ] identified ANGPTL3 as a crucial diagnostic gene connected to immune and renal disease-related pathways. This aligns with findings by Maluf et al [ 10 ], who in their genomic study observed a downregulation of angiogenesis-associated genes, including ANGPTL3, ANGPT2, and VEGF, in conditions of tubular atrophy and interstitial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of IFTA diagnosis based on mRNA expression, the quantity of samples and method of filtering variables were limited (Yang et al, 2022). With the progress of machine learning algorithms, early linear models such as Least Absolute Shrinkage and Selection Operator (LASSO), ridge regression (Ridge), elastic net (Enet), stepwise generalized linear models (Stepglm), linear discriminant analysis (LDA), partial least squares regression (plsRglm), and Naive Bayes have gradually evolved to non-linear models such as support vector machines (SVM), generalized boosted models (glmboost), random forest, gradient boosting machines (GBM), Extreme Gradient Boosting (XGBoost), and artificial neural networks (ANNs) and there are now many options available for the construction of disease diagnostic models.…”
Section: Introductionmentioning
confidence: 99%